Correction of Iron Deficiency in the Cardiorenal Syndrome - Donald S. Silverberg; Dov Wexler; Adrian Iaina; Doron Schwartz (International Journal of Nephrology)
Impaired energy metabolism is a feature of Congestive Heart Failure (CHF). Iron deficiency has been shown to reduce energy production in the cell in animals and humans. Iron deficiency is common in both Chronic Kidney Disease (CKD) and in CHF. Recent studies suggest that iron deficiency is an independent risk factor for mortality in CHF. Studies of correction of the anemia with intravenous (IV) iron in both CKD and CHF have shown an improvement in the anemia and, in some cases, in the renal function as well. Some CHF studies of correction of the iron deficiency have shown an improvement in cardiac function and structure as well as in exercise capacity and quality of life. This occurred independent of whether or not they had anemia, suggesting that the iron deficiency itself may be independently contributing to the worsening of the CHF and CKD. If future long-term studies confirm the safety and efficacy of IV iron in the treatment of iron deficiency in CKD and CHF, this will become a new addition to the therapeutic armamentarium of the cardiorenal syndrome, and parameters of iron deficiency will become part of the routine measurements performed in both CKD and CHF whether or not the patient is anemic.